2022
DOI: 10.1002/wsb.1306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating unoccupied aerial vehicles for estimating relative abundance of muskrats

Abstract: Due to muskrat (Ondatra zibethicus) population declines in North America, it is important to develop rapid, safe, and economical tools for estimating abundance over large spatial and temporal scales. During November 2020-February 2021, we assessed unoccupied aerial vehicles (UAVs) at Bear Creek Flooding State Wildlife Management Area in the northern Lower Peninsula of Michigan. We examined aerial red-greenblue (RGB) and thermal imagery for estimating the total number of muskrat houses during a snow-free and sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…To a lesser extent, it is also possible that deep snow cover led to houses being missed and to misidentification of other raised features on the orthoimagery. While Cline et al (2022) found greater detection accuracy of muskrat houses from aerial surveys conducted on a wetland under snow cover, which they attribute to the contrast and shadow cast by snow‐covered houses against the surrounding vegetation, the total snow depth at the time of their imagery collection was 15 cm. Snow depths in our study sites ranged from 5 cm to 35 cm during the dates of our imagery collection; houses in the wetlands under deeper snow cover may have had less definition and less visible contrast against their surroundings.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…To a lesser extent, it is also possible that deep snow cover led to houses being missed and to misidentification of other raised features on the orthoimagery. While Cline et al (2022) found greater detection accuracy of muskrat houses from aerial surveys conducted on a wetland under snow cover, which they attribute to the contrast and shadow cast by snow‐covered houses against the surrounding vegetation, the total snow depth at the time of their imagery collection was 15 cm. Snow depths in our study sites ranged from 5 cm to 35 cm during the dates of our imagery collection; houses in the wetlands under deeper snow cover may have had less definition and less visible contrast against their surroundings.…”
Section: Discussionmentioning
confidence: 96%
“…The use of other types of imagery also holds promise, either for alternative methods of automatic classification or to assist human aerial imagery observers with the classification of ambiguous structures. For example, Cline et al (2022) experienced some success in using thermal imaging to identify the vent holes at the top of muskrat houses, thus confirming the presence of active houses, although they noted that the technique was not reliable in all snow and temperature conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monitoring mammals using drones has been extensively studied [22][23][24][25][26][27][28][29][30][31][32][45][46][47][48][49][50][51]. Witt et al [32] compared spotlight counts and point counts to counts using a drone equipped with thermal cameras for direct detection of koalas (Phascolarctos cinereus) while flying the drone in predetermined transects.…”
Section: Similar Studiesmentioning
confidence: 99%